2021
DOI: 10.2116/analsci.21p139
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Width and Height of π* Peak in C K-XANES of Graphitic Carbons

Abstract: The relationship between the width and height of the π* peak on X-ray absorption near edge structure (XANES) in the C K region of graphitic carbons is investigated from XANES measurements and theoretical analysis. This relationship is herein named the "characteristic diagram of π* peak profile". Mechanically ground (MG) graphite experimentally exhibits a linear correlation on the diagram. To understand the linear correlation, C K-XANES of the graphitic hexagonal carbon layers are calculated using first-princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Based on modeling of zigzag and armchair edges, broader π* peaks or a shoulder leading the main peak by about 1 eV may be indicative of increased populations of edge carbon. 54 This does not appear to be the case in the spectra herein, suggesting that the total edge content of these treated fibers has not significantly changed. Lee et al identified a peak at 286.9 eV that was related to π* (C−O) for phenolic terminated basal planes.…”
Section: ■ Results and Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Based on modeling of zigzag and armchair edges, broader π* peaks or a shoulder leading the main peak by about 1 eV may be indicative of increased populations of edge carbon. 54 This does not appear to be the case in the spectra herein, suggesting that the total edge content of these treated fibers has not significantly changed. Lee et al identified a peak at 286.9 eV that was related to π* (C−O) for phenolic terminated basal planes.…”
Section: ■ Results and Discussionmentioning
confidence: 63%
“…They identified the (CC) 1s → π* peak at about 285.1 eV, and a (C–C) (1s → σ*) peak at about 292.5 eV. Based on modeling of zigzag and armchair edges, broader π* peaks or a shoulder leading the main peak by about 1 eV may be indicative of increased populations of edge carbon . This does not appear to be the case in the spectra herein, suggesting that the total edge content of these treated fibers has not significantly changed.…”
Section: Resultsmentioning
confidence: 67%